Building a Learning Society through the Coaching of Parents and Children in Taman Bacaan Masyarakat (TBM) - Syuraini, Syuraini; Jamna, Jamaris; Jalius, Jalius (Universitas Negeri Padang, 2019)
The person who is most responsible for the success of children is their parents. Because children born and raised by parents are the property of parents and cannot be contested. To carry out these heavy obligations, parents must have adequate knowledge and skills in order to achieve what they aspire to be, namely making children pious who are intelligent and of good character. The reality today is that there are still many parents who do not know that their role is very large in educating children so that they do not think and do not even make the maximum effort in educating children. Most parents submit their children's education to other people who are trusted, such as teachers at school, in the course and tutoring, and teachers at the Koran, so they do not pay attention to learning at home. The effect is a lot of personality that is not praiseworthy even failure in learning in school. To overcome this problem, parents and children are coaching through Community Reading Gardens. Keywords: Learning Society, Parents, Responsibility, Knowledge, Coaching